Strategi Komunikasi Pemasaran “Brain Coffee” Melalui Media Sosial Instagram - Marizka Dhia Ayu Nabilah Sandy, Dwi Prasetyo (DIGICOM : Jurnal Komunikasi dan Media, 2022)
Marketing communication is a marketing activity that seeks to disseminate information, influence, persuade and remind consumers directly or indirectly about the products being sold. The use of Instagram social media provides benefits for business people. Companies have different strategies in attracting consumers. Brain Coffee is a coffee shop in South Surabaya that uses social media Instagram as its promotional media. This research is to find out the marketing communication strategy carried out by Brain Coffee through Instagram social media. This study uses a qualitative descriptive method that describes a situation. The researcher analyzes the marketing communication strategy through the @braincoffee.id Instagram account. Data collection techniques using observation, interviews and documentation. The results of this study indicate that the marketing communication strategy carried out by Brain Coffee uses the concept of a communication mix, namely advertising, sales promotion, public relations, personal selling, direct selling. and interactive marketing and take advantage of Instagram's features consistently every day.